Vaccination coverage and its determinants of live attenuated hepatitis A vaccine among children aged 24-59 months in 20 rural counties of 10 provinces of China in 2016 - Xiaoli Liu; Chenlu Yang; Xueqi Qu; Nan Li; Xiaona Huang; Yuning Yang; Yiming Zhao; Yan Wang; Hong Zhou (Taylor & Francis Group, 2020)
Objective To understand one single dose coverage of live attenuated hepatitis A vaccine and its determinants among children aged 24-59 months in 20 rural counties of 10 provinces of China in 2016. Methods In 20 counties, using three-stage probability proportion to size sampling, 1979 children aged 24-59 months with a vaccination card were selected from 20 rural counties in 2016. Socio-demographic and socio-economic characteristics of children and their caregivers were acquired from face-to-face questionnaire survey and copies of the vaccination cards. We used multivariate logistic regression models to identify the determinants of one single dose coverage of live attenuated hepatitis A vaccine. Results In 2016, the overall one single dose coverage of live attenuated hepatitis A vaccine among children aged 24-59 months in rural areas of China was 77.1%. The adjusted analysis showed that being in second birth order (adjusted OR: 1.40; 95%CI: 1.03-1.90), being in third birth order or more (adjusted OR: 2.10; 95%CI: 1.26-3.51), being born at home (adjusted OR: 2.01; 95%CI: 1.04-3.88) and having the lowest per capita income of household (adjusted OR: 2.36; 95%CI: 1.11-4.99) were significantly related to being unvaccinated one single dose coverage of live attenuated hepatitis A vaccine against hepatitis A virus. Conclusion one single dose coverage of live attenuated hepatitis A vaccine was still at a low level in 20 rural counties of 10 provinces in China. To improve the coverage of live attenuated hepatitis A vaccine, the government should pay more attention to the disadvantaged groups, especially the children who were in second birth order or higher, or delivered at home, or who have the lowest per capita income of household.